Efficacy of omega-3 in the treatment of polycystic ovary syndrome. (April 2013) - Oner, G.; Muderris, I. I.
<x xml:space="preserve">Abstract</x> The purpose of this study was to evaluate the efficacy and safety of omega-3 in the treatment of polycystic ovary syndrome and to compare the clinical, hormonal, TNF-α and resistin levels in the patients treated with omega-3. A total of 45 non-obese PCOS women were studied. Women were treated with daily oral 1, 500 mg of omega-3 for 6 months. Body mass index (BMI), hirsutism score, fasting glucose and insulin levels were noted for each case. Hirsutism was assessed at 6-month intervals using the Ferriman–Gallwey (F–G) scoring system. Hormonal, TNF-α and resistin levels at 6 months of therapy were compared with baseline values. BMI, F–G scoring, insulin and HOMA levels decreased significantly during treatment, but glucose levels did not change. In the hormonal profile, serum LH and testosterone levels decreased and sex hormone-binding globulin levels increased significantly after the 6 months of therapy. On the other hand, TNF-α levels showed a significant increase, whereas resistin levels showed no change. Omega-3 may be also effective in improving hirsutism and insulin resistance in patients with PCOS.